2014
DOI: 10.1016/j.bbr.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of KCC3 in parvalbumin neurons leads to locomotor deficit in a conditional mouse model of peripheral neuropathy associated with agenesis of the corpus callosum

Abstract: Hereditary motor and sensory neuropathy associated with agenesis of the corpus callosum (HMSN/ACC or ACCPN) is an autosomal recessive disease caused by the disruption of the SLC12A6 gene, which encodes the K-Cl cotransporter-3 (KCC3). A ubiquitous deletion of KCC3 in mice leads to severe locomotor deficits similar to ACCPN patients. However, the underlying pathological mechanism leading to the disease remains unclear. Even though a recent study suggests that the neuropathic features of ACCPN are mostly due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…11 Intriguingly, parvalbumin-specific knockdown of KCC3 has also led to locomotor deficit phenotypes in mice, which supports our previous findings of KCC3 expression in these neurons. 16,17 Although this disease announces itself as a peripheral neuropathy, our findings of ongoing axonal atrophy in the white matter of the nervous system at the time of death indicate widespread ongoing axonal disease in the cerebral hemispheres as well. Intra-hemispheric disconnection and telencephalic spheroids may explain the psychotic symptomatology in this disease.…”
Section: Modern Pathology (2016) 29 962-976mentioning
confidence: 66%
“…11 Intriguingly, parvalbumin-specific knockdown of KCC3 has also led to locomotor deficit phenotypes in mice, which supports our previous findings of KCC3 expression in these neurons. 16,17 Although this disease announces itself as a peripheral neuropathy, our findings of ongoing axonal atrophy in the white matter of the nervous system at the time of death indicate widespread ongoing axonal disease in the cerebral hemispheres as well. Intra-hemispheric disconnection and telencephalic spheroids may explain the psychotic symptomatology in this disease.…”
Section: Modern Pathology (2016) 29 962-976mentioning
confidence: 66%
“…However, whether these effects are driven by disrupted RVD in neurons or glia had remained unclear until two recent reports demonstrated that neuron-specific knockdown of KCC3 sufficed to recapitulate the neuropathology [63,64]. In the first study, CRE recombinase-mediated KCC3 deletion was driven by the synapsin promoter, thus targeting all neurons [63].…”
Section: Kcc3 Is Essential For Nervous System Cell Volume Regulationmentioning
confidence: 99%
“…First, Shekarabi et al showed that specific targeting of KCC3 deletion in neurons (using synapsin I-CRE) was sufficient to recapitulate the phenotype of the global knockout [10]. Second, we demonstrated that deletion of KCC3 in proprioceptive sensory neurons (driven by parvalbumin-CRE) also recapitulated the proprioceptive and locomotor deficits observed in the global and synapsin I CRE-induced knockout mice [11]. In agreement with a neuronal origin, driving CRE specifically in Schwann cells by using desert hedgehog-CRE did not result in any observable phenotype [11].…”
Section: Cellular Origin Of the Kcc3-induced Neuropathymentioning
confidence: 64%
“…Second, we demonstrated that deletion of KCC3 in proprioceptive sensory neurons (driven by parvalbumin-CRE) also recapitulated the proprioceptive and locomotor deficits observed in the global and synapsin I CRE-induced knockout mice [11]. In agreement with a neuronal origin, driving CRE specifically in Schwann cells by using desert hedgehog-CRE did not result in any observable phenotype [11]. The fact that phosphorylation of K-Cl cotransporter leads to inhibition while dephosphorylation leads to its activation is well appreciated in the field since the early 1990s [12].…”
Section: Cellular Origin Of the Kcc3-induced Neuropathymentioning
confidence: 98%
See 1 more Smart Citation